Analisis Pembelajaran Daring Di Masa Pandemi Covid-19 - Esterlin Stevani; Kuwing Baboe; Sundari Sundari (FKIP, Universitas Palangka Raya, 2021)
Since the Covid-19 pandemic has made the learning system that was originally face-to-face turned into online learning using applications such as Zoom Meeting, Google Classroom, Google Meet, WhatsApp and others. The purpose of the study was to analyze online learning during the Covid-19 pandemic on students' understanding of the Economic Education Study Program FKIP Palangka Raya University in 2020. The focus of the research was the 2017-2019 students of the Economic Education Study Program FKIP Palangka Raya University. Researchers selected students from the 2017-2019 class who experienced a change in learning from face-to-face to online learning by looking at student understanding while online supported by the student Achievement Index before the Covid-19 pandemic (offline learning) and after the Covid-19 pandemic (online learning). The research uses qualitative methods. Data collection by distributing questionnaires on google forms, interviews via whatsapp with informants, and documentation. Checking the validity of the data through the credibility test, transferability test, dependability test and confirmability test. The result of the research is that online learning does not fully provide understanding to students, because it is constrained by quotas, unstable signals, increased costs during online learning, students work during Covid-19 so that students do not focus on online learning. In addition, online learning reduces students' enthusiasm for learning. It was concluded that students did not fully understand the material during online learning due to network factors and the lack of enthusiasm for student learning.